The effect of therapy of the lower urinary tract symptoms due to prostatic benign enlargement on erectile function - Štraus, Anja (Array, 2020)
Background: Benign prostatic enlargement is the most common benign disease in men. The main cause for the emergence of benign prostatic enlargement is sexual hormone testosterone. Under the influence of enzyme 5-alpha reductase testosterone turns into active dihydrotestosterone, which is then combined with receptors and causes the growth of the prostate. Benign prostatic enlargement can cause the lower urinary tract symptoms. One of the treatment options of lower urinary tract symptoms due to benign prostatic enlargement is the treatment with medicaments – inhibitors 5-alpha reductase. Like any other medicament, this one can also have unpleasant side effects, between others reduced erectile function and reduced libido. Methods: We used the International Index of Erectile Function (IIEF-5), Quality of Erection Questionnaire (QEQ), and demographic data. Results: Men with benign prostatic enlargement have problems with keeping an erection even before starting the therapy with medicaments. After the therapy with inhibitors 5-alpha reductase the results of the research show that on the erectile function scale, there are no significant differences between the first and second measurement, but on the erectile dysfunction scale expected differences occur – the functionality decreases. We also noticed that the independent variables of age and employment status have influence on the result of medicament treatment in the way that older participants in the study have more issues with erectile function than younger ones. Secondly, the men in retirement have more problem than employed men. There were no noticeable connections between the level of completed education and the profession of the participants. Conclusions: The results of the research were expected, according to the previously consulted literature, where the side effects of treatment with medicaments inhibitors 5-alpha reductase were already mentioned. The effects that the treatment has on erectile functio